EVALUATION OF FLOTATION METHODS (33% ZNSO4 AND SATURATED NACL) AND SEDIMENTATION (0.9% NaCl AND DISTILLED WATER) IN PIG FECES - Agamonanza, Freddy; Wulansari, Keke Putri; Rakhmawati, Aprilia (STIKes Mitra Keluarga, 2026)
Introduction: Gastrointestinal parasitic infections in pigs remain a significant problem, especially in smallholder farming systems with traditional management practices. Parasite detection is generally carried out through fecal examination, but the sensitivity of the results is greatly influenced by the methods and reagents used. This study seeks to assess and contrast the efficacy of flotation and sedimentation techniques in identifying parasite eggs and larvae in pig feces from Marga Sari Village, Tangerang Regency. Research Methods: A comparative descriptive study using fifteen pig feces samples obtained through purposive sampling. Each sample was examined using four examination methods, namely the flotation method with a 33 ZnSO4 solution, the flotation method with a saturated NaCl solution, the sedimentation method with a 0.9 NaCl solution, and the sedimentation method using distilled water. All samples were examined once using each method, resulting in a total of 60 preparations observed. Microscopic examination was performed to identify the presence and type of parasite eggs and larvae based on their morphological characteristics. Research Results: The flotation method using a 33 ZnSO4 solution showed the highest percentage of positive samples, namely 53.3, followed by the saturated NaCl flotation method at 40.0. The sedimentation method with a 0.9 NaCl solution and distilled water showed positive percentages of 33.3 and 26.7, respectively. Ascaris lumbricoides eggs were the most commonly found parasites, while hookworm eggs were only detected using the flotation method. Conclusion: The flotation method, particularly using a 33 ZnSO4 solution, is the most sensitive method for detecting parasite eggs in pig feces. A combination of flotation and sedimentation methods is recommended to obtain a more comprehensive diagnosis of gastrointestinal parasites.